2002
DOI: 10.21273/horttech.12.4.727
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Container Nursery Irrigation Practices in Georgia

Abstract: A 2001 survey of 102 nurseries that were members of the Georgia Green Industry Association was conducted to assess irrigation practices of container ornamental nurseries. Mean nursery size was 64 acres (26 ha) and mean annual revenue was about $3 million. About 50% of the irrigation water was from wells and the other 50% came from surface sources, such as collection basins. Irrigation in smaller containers, including #1, #3, and #5, was applied primarily by overhead methods, while larger containers (#7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
0
16
1
4
Order By: Relevance
“…Specifically, the frequency of runoff collection doubled (11% to 22%), the recycling of runoff water doubled (6% to 14%) and run-off water-quality monitoring (12% to 17%) and record keeping (8% to 17%) increased. The adoption of runoff management practices was low compared with surveys in Alabama, Georgia and Florida, which found that 75%, 45% and 50% of nurseries, respectively, collected runoff (Fain et al 2000;Garber et al 2002;Schoene et al 2006).…”
Section: Management Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, the frequency of runoff collection doubled (11% to 22%), the recycling of runoff water doubled (6% to 14%) and run-off water-quality monitoring (12% to 17%) and record keeping (8% to 17%) increased. The adoption of runoff management practices was low compared with surveys in Alabama, Georgia and Florida, which found that 75%, 45% and 50% of nurseries, respectively, collected runoff (Fain et al 2000;Garber et al 2002;Schoene et al 2006).…”
Section: Management Practicesmentioning
confidence: 99%
“…Some studies have found considerable adoption of selected management practices by nurseries. For example, surveys of U.S. container production nurseries in Alabama and Georgia found that about half or more captured runoff water, and more than half used vegetative filter strips (Fain et al 2000;Garber et al 2002). Other practices may be less commonly adopted.…”
mentioning
confidence: 99%
“…Growers reported plant needbased watering as a BMP (Garber et al, 2002;Mack et al, 2017). Garber et al (2002) surveyed Georgia growers and found that the frequency of growers that use need-based watering (17%) was equal to that of water recycling as a water conservation practice.…”
Section: Irrigation Managementmentioning
confidence: 99%
“…Growers reported plant needbased watering as a BMP (Garber et al, 2002;Mack et al, 2017). Garber et al (2002) surveyed Georgia growers and found that the frequency of growers that use need-based watering (17%) was equal to that of water recycling as a water conservation practice. Mack et al (2017) found that plant needs-based watering was rated 8.3/10 on a Likert scale of use (least used = 0, most used = 10) among surveyed Virginia growers.…”
Section: Irrigation Managementmentioning
confidence: 99%
See 1 more Smart Citation